The Influence of Career Expectations, Self-Efficacy and Social Environment on Students' Interest in Continuing Their Studies to Higher Education with Parental Income as a Moderating Variable on Grade XII Students of State Senior High Schools in Bojonegoro - Utomo, Eko Budi; Surjanti, Jun; Hakim, Luqman (Jurnal Pendidikan Edutama, 2025)
This research is motivated by the low interest of students in schools on the outskirts of Bojonegoro to continue their studies to college. This study aims to analyze the influence of career expectations, self-efficacy, and social environment on students' interest in continuing their studies to college, with parental income as a moderating variable. This study uses a quantitative approach using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The study was conducted in four public senior high schools in Bojonegoro Regency with subjects of grade XII students. The sample was determined proportionally at 100 students from a total population of 825 students. Data were collected using a questionnaire. The results showed that career expectations, self-efficacy, and social environment significantly influence students' interest in continuing their studies. Parental income was shown to significantly moderate the relationship, but at a weaker level. The conclusion of this study emphasizes the important role of parental income in determining the effectiveness of psychological and social factors on students' decisions to continue their studies. Therefore, affirmative policy support and educational interventions are needed for students from low-income families.